MHD mixed convection stagnation-point flow of a micropolar fluid in a porous medium towards a heated stretching sheet with thermal radiation - Pal, Dulal; Chatterjee, Sewli (Mathematical Modelling and Analysis, 2012)
The present investigation is concerned with the study of heat and mass transfer characteristics on MHD boundary layer flow of an electrically conducting micropolar fluid over a non-isothermal stretching sheet embedded in a porous medium of variable thermal conductivity by applying prescribed heat flux for the heating processes. The thermal boundary layer equation takes into account of Ohmic dissipation due to transverse magnetic and electric fields. The governing system of partial differential equations is transformed into a system of non-linear ordinary differential equations using similarity transformation. The transformed non-linear coupled differential equations are linearized by quasi-linearization method and then solved very efficiently by finite-difference method. Attention has been focused to study the effects of various physical parameters on velocity, temperature and concentration in the boundary layer. Numerical data for the local skin friction coefficient, surface temperature and surface solutal concentration have also been tabulated for various parametric conditions.